Pregibit: A family of discrete choice models - Chu-ping C. Vijverberg; Wim P. Vijverberg (Institute for the Study of Labor (IZA), 2012)
The pregibit discrete choice model is built on a distribution that allows symmetry or asymmetry and thick tails, thin tails or no tails. Thus the model is much richer than the traditional models that are typically used to study behavior that generates discrete choice outcomes. Pregibit nests logit, approximately nests probit, loglog, cloglog and gosset models, and yields a linear probability model that is solidly founded on the discrete choice framework that underlies logit and probit.
urn:nbn:de:101:1-201205027307
Keywords: C25; G21; I21; 330; discrete choice; asymmetry; logit; probit; post-secondary education; mortgage application; Diskrete Entscheidung; Logit-Modell; Theorie